Alkenes as Chelating Groups in Diastereoselective Additions of Organometallics to Ketones - Raffier, Ludovic (American Chemical Society, 2014)
[Image: see text] Alkenes have been discovered to be chelating groups to Zn(II), enforcing highly stereoselective additions of organozincs to β,γ-unsaturated ketones. (1)H NMR studies and DFT calculations provide support for this surprising chelation mode. The results expand the range of coordinating groups for chelation-controlled carbonyl additions from heteroatom Lewis bases to simple C–C double bonds, broadening the 60 year old paradigm.